2014
DOI: 10.1007/s10461-014-0694-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women Living with HIV (WLH) Supported at Clinics by Peer WLH: A Cluster Randomized Controlled Trial

Abstract: Throughout Africa, Peer Mentors who are women living with HIV (WLH) are supporting pregnant WLH at antenatal and primary healthcare clinics (McColl in BMJ 344:e1590, 2012). We evaluate a program using this intervention strategy at 1.5 months post-birth. In a cluster randomized controlled trial in KwaZulu-Natal, South Africa, eight clinics were randomized for their WLH to receive either: standard care (SC), based on national guidelines to prevent mother-to-child transmission (4 clinics; n = 656 WLH); or an enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 30 publications
5
128
0
1
Order By: Relevance
“…l educational (n = 5) [188][189][190]192,271 l social support (n = 5) 149,[201][202][203][204] l pharmacological agents or supplements (n = 1) 213 l midwifery-led interventions (n = 3) [221][222][223] l organisation of maternity care (n = 0) l CAM or other (n = 0).…”
Section: Summary Of Results From Network Meta-analysis For Universal mentioning
confidence: 99%
See 2 more Smart Citations
“…l educational (n = 5) [188][189][190]192,271 l social support (n = 5) 149,[201][202][203][204] l pharmacological agents or supplements (n = 1) 213 l midwifery-led interventions (n = 3) [221][222][223] l organisation of maternity care (n = 0) l CAM or other (n = 0).…”
Section: Summary Of Results From Network Meta-analysis For Universal mentioning
confidence: 99%
“…psychological (n = 30) 61,121,148, 2. educational (n = 17) [180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196] 3. social support (n = 11) 149,[197][198][199][200][201][202][203][204][205][206] 4. pharmacological agents or supplements (n = 10) [207][208][209][210][211][212][213][214][215][216] 5. midwifery-led interventions (n = 9)…”
Section: Intervention Classmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the peer element of the intervention that is vital, the individual nature of the intervention reflects the no one-size-fits-all finding of our study while providing a clear structure to enable the effects of the intervention to be evaluated. A number of studies in other HIV settings have found that patients benefit from peer support, [87][88][89] and the evidence in the UK so far has been promising but limited in scale. 90 DOI: 10.3310/hsdr05130 HEALTH SERVICES AND DELIVERY RESEARCH 2017 VOL.…”
Section: Peer and Community Support (+Ve)mentioning
confidence: 99%
“…Participação em programas de prevenção 13,16,[18][19][20][23][24][25][26][27][28] Acolhimento da equipe de saúde 11,16,21,24 Educação em saúde 20 Conforto das condições de saúde 24 Divulgação do estado sorológico [16][17][18][19] Aderir às medidas de profilaxia da TV 11,[16][17][18][19] Repercussões na saúde sexual 13 Deus e a fé 15,24,27 Divulgação do estado sorológico 29 Motivação para aceitar o diagnóstico e o tratamento 24 repercussões na saúde sexual: consideraram-se com maior capacidade para negociar o planejamento familiar, além do uso de preservativo, e solicitar ao companheiro que realizasse o teste de anticorpos do HIV.…”
Section: Suporte Instrumentalunclassified